Similarities and differences in the biochemical and enzymological properties of the four isomaltases from Saccharomyces cerevisiae. Issue 1 (15th February 2014) - Deng, Xu; Petitjean, Marjorie; Teste, Marie-Ange; Kooli, Wafa; Tranier, Samuel; François, Jean Marie; Parrou, Jean-Luc
Abstract : The yeast Saccharomyces cerevisiae IMA multigene family encodes four isomaltases sharing high sequence identity from 65% to 99%. Here, we explore their functional diversity, with exhaustive in‐vitro characterization of their enzymological and biochemical properties. The four isoenzymes exhibited a preference for the α‐(1, 6) disaccharides isomaltose and palatinose, with Michaëlis–Menten kinetics and inhibition at high substrates concentration. They were also able to hydrolyze trisaccharides bearing an α‐(1, 6) linkage, but also α‐(1, 2), α‐(1, 3) and α‐(1, 5) disaccharides including sucrose, highlighting their substrate ambiguity. While Ima1p and Ima2p presented almost identical characteristics, our results nevertheless showed many singularities within this protein family. In particular, Ima3p presented lower activities and thermostability than Ima2p despite only three different amino acids between the sequences of these two isoforms. The Ima3p_R279Q variant recovered activity levels of Ima2p, while the Leu‐to‐Pro substitution at position 240 significantly increased the stability of Ima3p and supported the role of prolines in thermostability. The most distant protein, Ima5p, presented the lowest optimal temperature and was also extremely sensitive to temperature. Isomaltose hydrolysis by Ima5p challenged previous conclusions about the requirement of specific amino acids for determining the specificity for α‐(1, 6) substrates. We finally found a mixed inhibition by maltose for Ima5p while, contrary to a previous work, Ima1p inhibition by maltose was competitive at very low isomaltose concentrations and uncompetitive as the substrate concentration increased. Altogether, this work illustrates that a gene family encoding proteins with strong sequence similarities can lead to enzyme with notable differences in biochemical and enzymological properties. Abstract : Isomaltases (Imap) preferably cleave α‐(1, 6) bonds, yet show clear substrate ambiguity. With only 3 different aa, Ima3p activities and thermostability diverge from Ima2p. The most distant protein, Ima5p, is extremely sensitive to temperature. Ima5p nevertheless displays most of the same catalytic properties as Ima1p and Ima2p. Ima5p challenges previous conclusions about specific aa needs for the active site.